Influencia de los medios de comunicación de radio y televisión en la conducta de los niños/as de 4to de primaria de la I.E N°00614 del distrito de Nueva Cajamarca - Sosa Velasquez, Lilibeth Yacory (2013)
This research aims to determine the correlation between media and behavior of children of the fourth grade primary education school No. 00614 Nueva Cajamarca district. The study is important because it allows to describe the influence of mass media: radio and television on children's behavior. The central objective of the research was to determine the influence of media broadcasting in the behavior of chi!dren, the fourth grade of primary education in the school No. 00614, and the specific objectives were to describe the behavior of children in the fourth grade of primary education, describe the importance of media in radio and television children, and analyze the influence of the media on the behavior of children in the fourth grade primary education and infer the results of the relationship between the media in the behavior of children. The media is based on the work of Anal Frailee (1995), Feshbach and Singer (1970), Paul Blakely (1958) and Katzy and Lazarsfeld (1979) and behavior is based on studies of Castro, J. (2002), Fishbein and Ajzen, 1975 in Bolívar, 1995). Theories allow us to pose the following hypothesis: The media radio and te!evision will have significant influence on the behavior of children of the fourth grade of primary education 00614 El Nueva Cajamarca District, 2011. Methodologically, the research design was descriptive and correlational study, with a sample of 147 children of school No. 00614 in the district of Nueva Cajamarca, and in the process of statistical analysis was obtained by accepting the central hypothesis or research a confidence of 95% and the value obtained from the Pearson correlation coefficient being a positive correlation mean and which is explained by the 29.26% of the popu!ation.